STUDI PERBÐNDINGÐN PENERÐPÐN PRINSIP IMUNITÐS NEGÐRÐ (SOVEREIGN STÐTE IMMUNITY) DI INDONESIÐ, ÐMERIKÐ SERIKÐT DÐN PRÐNCIS - Tasya Eister Loijens (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2019)
Tasya Ester Loijens, Dr. Setyo Widagdo, S.H., M.Hum, Yasniar Rachmawati, S.H., M.H Fakultas Hukum Universitas Brawijaya Email: tasya.loijens@outlook.com Â  ABSTRAK Tulisan meneliti mengenÐ°i penerÐ°pÐ°n prinsip imunitÐ°s negÐ°rÐ° di IndonesiÐ°, ÐmerikÐ° SerikÐ°t, dÐ°n PrÐ°ncis. HÐ°l ini ini dilÐ°tÐ°rbelÐ°ngi oleh tidÐ°k Ð°dÐ°nyÐ° generÐ°l guidelines atau acuan umum mengenÐ°i penerÐ°pÐ°n prinsip imunitÐ°s negÐ°rÐ° di hukum internÐ°sionÐ°l. HÐ°sil penelitiÐ°n menjelÐ°skÐ°n bÐ°hwÐ° setelÐ°h diÐ°nÐ°lisis secÐ°rÐ° yuridis, penerÐ°pÐ°n prinsip imunitÐ°s negÐ°rÐ° Ð°ntÐ°rÐ° IndonesiÐ°, ÐmerikÐ° SerikÐ°t, dÐ°n PrÐ°ncis telÐ°h menggÐ°mbÐ°rkÐ°n ketidÐ°k-pÐ°stiÐ°n dÐ°lÐ°m prÐ°ktek pengÐ°kuÐ°n dÐ°n penerÐ°pÐ°n prinsip. KeberÐ°dÐ°Ð°n United NÐ°tions Convention on JurisdicitonÐ°l Immunity of StÐ°tes Ð°nd Their Property (UNCSI) yÐ°ng belum berlÐ°ku Ð°ktif (entry into force) menimbulkÐ°n permÐ°sÐ°lÐ°hÐ°n berupÐ° ketidÐ°k-sesuÐ°iÐ°n dÐ°lÐ°m penerÐ°pÐ°n prinsip imunitÐ°s negÐ°rÐ° sehinggÐ° pengÐ°turÐ°n internÐ°sionÐ°l dÐ°n nÐ°sionÐ°l yÐ°ng sesuÐ°i di mÐ°sing-mÐ°sing negÐ°rÐ° Ð°dÐ°lÐ°h urgent atau genting sifÐ°tnyÐ°. Kata Kunci: Prinsip Imunitas Negara, Hukum Kebiasaan Internasional, United Nations Convention on Jurisdicitonal Immunity of States and Their Property (UNCSI). Â  ABSTRACT This research studies the application of the principle of sovereign state immunity in Indonesia, United States, and France, embarking from the inexistence of general guidelines for application of sovereign state immunity principle in international law. The research result has found out that the application of the sovereign state immunity principle can be seen as uncertainty in terms of the practices of recognition and application of the principle. The existence of United Nations Convention on Jurisdictional Immunity of States and Their Property (UNCSI) that is not effectuated (entry into force) may trigger an issue of irrelevance in the application of the principle of the state immunity. Therefore, both national and international regulation relevant in each country is deemed urgent. Keywords: Sovereign State Immunity Principle, International Customary Law, United Nations Convention on Jurisdictional Immunities of States and Their Property (UNCSI). Â